Job creation in tight and slack labor markets - Lukas Buchheim; Martin Watzinger; Matthias Wilhelm (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Do investment programs create more jobs in tight or in slack labor markets? We study this question using data from a large, long-term photovoltaic invest scheme in Germany. Comparing counties with high and low unemployment both over time and across space, we find that photovoltaic installations created at least twice as many jobs in slack than in tight labor markets. Our results suggest that the differences in job-creation are not driven by changes in the composition or prices of investment, capital-labor substitution, or regional migration. This leaves crowding-out as the most plausible mechanism.
Keywords: E24; E62; J23; R23; 330; Local Employment Multiplier; State-dependent Multiplier